Association of Obesity with Chronic Idiopathic Urticaria at Birat Medical College and Teaching Hospital - Choudhary, Dilip; Shrestha, Sabrina Yamu (Birat Journal of Health Sciences, 2020)
Introduction: A frequent association between metabolic syndrome with chronic idiopathic urticaria has been suggested by many studies but thorough investigations about the influence of obesity and overweight on chronic spontaneous urticaria has not been done. Objectives: To find out the association of obesity with chronic idiopathic urticaria. Methodology: Patients with chronic idiopathic urticaria were assessed for the body weight, height, body mass index, age of disease onset and duration of the disease. Results: A total of 151 patients were enrolled in the study and among them 64 % were females as compared to 26 % males. The age of the patients included ranged from 17 years to 77 years. Among the patients included in study, 69 % of the patients suffering from CIU were found to be overweight and obese. The body mass index of the patient included ranged from 16.7 to 34.2 with mean of 24.3+/-4.3. Conclusion: There is a relatively high incidence of urticaria among the people who are obese and overweight.